Chapter Il fascismo immaginario di Odon Por - DARDI, MARCO (Studi e saggi, 2021)
A minor but frequent editorialist and contributor to the Fascist press over the 1930s, Odon Por reached the apex of his visibility when he joined Ezra Pound in the attempt to promote policies based on Major Douglas's Social Credit and Silvio Gesell's Stamp Scrip. Drawing on various archival sources, the chapter reconstructs Por's international background, the political protections that allowed him to occupy comfortable positions in the regime's institutions, and his ideological itinerary from revolutionary syndicalism to guild socialism and from here to a fascism which was more imagined than real. His case is a typical illustration of the appeal that the Italian corporatist model held for anti-capitalist movements in inter-war Europe.